Studi Eksperimen Uji Kuat Tekan, Geser dan Tarik Lentur Pasangan Batu Merah Lokal Produksi Daerah Blitar - rustam, rustam; naibaho, armin; Pandulu, Galih Damar (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2017)
On a thesis is conducting research and testing a red stone against strong press , slide and pull in a pair of red stone that came from three local namely kecamatan Wates the sample, Sanan kulon sub-district , and the kecamatan Srengat all located in the Blitar district . The purpose of experiments in this research is to observe strong destroyed the couple local brick with the volume of a mixture of one part portland cement: 3 of the tide of sand, and observing strong lekatan sliding a pair of bricks with a mixture of the volume of mortar that same with strong destroyed namely 1 part portland cement: 3 of the sand on thesis is conducting research and testing a red stone against strong press, slide and pull in a pair of local red stone that came from three regions in the sample is Wates, Sanan kulon subdistrict , and the kecamatan Srengat all located in the Blitar district. The results of testing strong press a pair of red stone of each region production different , the third in production after the test , a red stone from the production of Wates regions have the power to press the average highest namely by fk = 35 , 67 kg per cm2 .The order of strong press next namely those Sanan kulon of fk = 33,52 kg per cm2 Srengat areas later by fk = 32,20 kg per cm2. Sliding strong performance also show different numbers at each region production bricks from other regions Wates = fcs the average 5.44 kg per cm2, Sanan kulon fcs the average = 4,77 kg per cm2 Srengat areas later fcs an average of = 4,06 kg per cm2. Test shows a strong sliding also different in each region production of bricks from the fcs Wates average = 5.44 kg per cm2 , Sanan kulon fcs average = 4,77 kg per cm2 areas later an average of fcs Srengan = 4,06 kg per cm2 . To vigorous pull pliable also shows as distinct from each origin its production that is, strong pull pliable regions of Wates fcs = 2.17 kg per cm2, strong pull pliable Sanan kulon fcs = 2,08 kg per cm2 , strong pull pliable Srengat regions fcs = 8 kg per cm2 Keywords: Brick, strong press, strong sliding, strong pull pliable, blitar